1995
DOI: 10.1002/aja.1002030206
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation pattern of capillary endothelial cells in chorioallantoic membrane development indicates local growth control, which is counteracted by vascular endothelial growth factor application

Abstract: The density and distribution of whole mount BrdU-anti-BrdU labeled endothelial cells (days 6 1 5 ) in the chick chorioallantoic membrane (CAM) was analyzed with computer-assisted microscopy. A significant loss of proliferative activity was noted after day 1 0 the density of labeled nuclei (in mm-2) decreased from a median 7.78 (days 6,8, 10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 45 publications
5
50
1
1
Order By: Relevance
“…5A-D) are compatible with those in real microvascular networks (Clark, 1991;Ellsworth et al, 1987;Honda and Yoshizato, 1997;Kurz et al, 1995;Less et al, 1997;Lichtenbeld et al, 1996;Lipowsky et al, 1978;Lipowsky and Zweifach, 1974;Pries et al, 1990Pries et al, , 1997Renkin, 1988). Moreover, in our random data samples, we find high pressure and low shear stress in and near the capillary region, because some branches may be (temporarily) not perfused -a situation that frequently occurs in living systems.…”
Section: Hemodynamics and Biomass Distributionsupporting
confidence: 87%
“…5A-D) are compatible with those in real microvascular networks (Clark, 1991;Ellsworth et al, 1987;Honda and Yoshizato, 1997;Kurz et al, 1995;Less et al, 1997;Lichtenbeld et al, 1996;Lipowsky et al, 1978;Lipowsky and Zweifach, 1974;Pries et al, 1990Pries et al, , 1997Renkin, 1988). Moreover, in our random data samples, we find high pressure and low shear stress in and near the capillary region, because some branches may be (temporarily) not perfused -a situation that frequently occurs in living systems.…”
Section: Hemodynamics and Biomass Distributionsupporting
confidence: 87%
“…The former has been implicated in vascular remodeling within adult tissues (Maisonpierre et al, 1997), whereas the latter is known to be essential for pericyte recruitment in the retina (Benjamin et al, 1998), brain (Hellstrom et al, 1999, and placenta (Ohlsson et al, 1999). Notably, the application of PDGF-B to fully developed CAMs leads to an abundant formation of larger pre-and postcapillary microvessels but does not amplify capillary meshes (Oh et al, 1998), whereas exogenous VEGF-A affects the capillary plexus and terminal feeding vessels, but has no influence on larger microvessels (Wilting et al, 1993;Kurz et al, 1995). Our assumption that endothelial cells respond to local challenges when initiating IBR is strongly supported by two recent observations: endothelial grafting in the chick-quail system showed that expression of the arterial marker ephrin-B2 depends on hemodynamics or local environment (Othman-Hassan et al, 2001); and serial section histology demonstrated intussusceptive remodeling in conditions of severely altered blood flow during tissue repair or tumor angiogenesis (Patan et al, 2001a,b).…”
Section: Possible Molecular Mechanisms Involved In Vascular Remodelingmentioning
confidence: 99%
“…In the CAM, intussusceptive microvascular growth (IMG; Caduff et al, 1986;Burri and Tarek, 1990) expands the capillary plexus (Patan et al, 1993;Schlatter et al, 1997) from which arterial and venous feeding vessels emerge by means of intussusceptive arborization (IAR) (Djonov et al, 2000a,b). The vascular bed of the CAM expands at an extraordinary speed for approximately 1 week by means of IMG and endothelial proliferation in capillaries, the later process ceasing at around incubation day 12 (E12) (Kurz et al, 1995). Simultaneously, the vascular bed is transformed from a single layer of capillaries into a twolayered system (by means of IAR): the gas-exchanging capillary plexus invades the chorionic epithelium, whereas arteries and veins remain "underneath" the capillary plexus displaying a typical bifurcation pattern.…”
Section: Introductionmentioning
confidence: 99%
“…At day 11, this falls to 2% and remains low throughout the remaining incubation period. An investigation by Kurz et al (1995) of the presence of bromodeoxyuridine-labeled endothelial cells in the growing CAM from day 6 to day 15 revealed a significant (Ͼ50%) loss of proliferative activity at day 10 (intermediate phase) in comparison with day 6 (sprouting phase). After day 10, proliferative activity decreased further, and at days 14 and 15 (late phase), dividing cells were Ͻ10% of the value of day 6.…”
Section: Morphometric Evaluation Of Cam Vascular Growthmentioning
confidence: 99%